2021
DOI: 10.3390/ijms222111917
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Hyaluronic Acid Inhibits IL-1β-Induced Synovial Inflammation and Macrophage Polarization through the GRP78-NF-κB Signaling Pathway

Abstract: Recent evidence has suggested that synovial inflammation and macrophage polarization were involved in the pathogenesis of osteoarthritis (OA). Additionally, high-molecular-weight hyaluronic acid (HMW-HA) was often used clinically to treat OA. GRP78, an endoplasmic reticulum (ER) stress chaperone, was suggested to contribute to the hyperplasia of synovial cells in OA. However, it was still unclear whether HMW-HA affected macrophage polarization through GRP78. Therefore, we aimed to identify the effect of HMW-HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
(66 reference statements)
4
31
0
Order By: Relevance
“…In addition, HA is negatively correlated with the production of IL‐1β‐stimulated MMPs and free radicals, 39 thereby mitigating chondrocyte apoptosis and articular cartilage degeneration. Interestingly, HA even showed protective role in tissue‐engineered cartilage in the presence TNF‐α via upregulation of VEGFA and ANKRD37 genes 40 . Recently, cellular senescence have been viewed as a critical factor influencing cartilage loss and joint inflammation 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HA is negatively correlated with the production of IL‐1β‐stimulated MMPs and free radicals, 39 thereby mitigating chondrocyte apoptosis and articular cartilage degeneration. Interestingly, HA even showed protective role in tissue‐engineered cartilage in the presence TNF‐α via upregulation of VEGFA and ANKRD37 genes 40 . Recently, cellular senescence have been viewed as a critical factor influencing cartilage loss and joint inflammation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HA even showed protective role in tissue-engineered cartilage in the presence TNF-α via upregulation of VEGFA and ANKRD37 genes. 40 Recently, cellular senescence have been viewed…”
Section: N-ha Exerts Anti-inflammatory Ability Through Attenuating Ce...mentioning
confidence: 99%
“…The pro-inflammatory pattern of IL-1β indicates that it can participate in the occurrence of a variety of inflammatory diseases. It has been reported that IL-1β can induce liver injury and inflammation in mice, and participate in the formation of systemic inflammation, RA, periodontitis and secondary inflammatory injury in the brain caused by asthma [61][62][63][64][65].…”
Section: Il-1βmentioning
confidence: 99%
“…[ [167][168][169][170][171][172] Red Ginseng Reported dual regulation of oxidative stress and increases in Bifidobacteria and Akkermansia gut bacteria. [173] Limosilactobacillus fermentum strains Supplementation with the probiotic mix reduced both inflammation and oxidative stress.…”
Section: Hyaluronic Acidmentioning
confidence: 99%